Cell membrane coating integrity affects the internalization mechanism of biomimetic nanoparticles - Lizhi Liu (Nature Portfolio, 2021)
Cell membrane coating of nanomaterials has become an attractive method of improving targeting, residence and biocompatibility. Here, the authors demonstrated that most nanoparticles are only partially coated by standard methods, and show the coating degree can impact the biological fate of nanoparticles.